LEGAL ANALYSIS OF DRUG ABUSE LAW TREATMENT THROUGH A RESTORATIVE JUSTICE APPROACH TO THE COUNTRY'S ECONOMY - Ariel Hermanus Gumalang; Lesza Lombok; Feibe Engeline Pijoh (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
Law evolves continually from the past to the present, aiming to improve various aspects, particularly the implementation of justice. One significant development is Restorative Justice, which shifts the focus in the criminal justice system towards justice for both victims and perpetrators, including alternative punishments like social work. The term "narcotics" often causes people to recoil in fear due to the severe negative impacts and numerous victims associated with these illegal substances. This concern extends widely, particularly among parents who worry about their children's associations. Recently, the issue has escalated to become a widespread concern for all segments of society. this research is to find out the regulations for the use of restorative justice in drug abuse cases and to determine the effect of criminal acts of drug abuse on the country's economy. By using normative legal method, the author finds that Restorative Justice is a shift in the criminal justice system that prioritizes justice for both victims and perpetrators, including alternative punishments like social work. It is regulated by various laws and emphasizes rehabilitation for narcotics abusers, recognizing them as both perpetrators and victims. The illegal drug trade has increased social, health, and economic impacts, with drug abuse leading to crime and social insecurity. Economic pressures drive abusers to commit crimes such as theft and robbery. According to data, Indonesia's state losses due to drugs have significantly risen, reaching IDR 84.7 trillion in 2017. Additionally, the UNODC reported a three-fold increase in opium production since 2006 in Southeast Asia's Golden Triangle, threatening regional stability and law enforcement.